Enhancing Urban Waste Management: An IoT-based Automated Trash Volume Monitoring System - Ayu Latifah; Dede Kurniadi; Muhammad Sanusi (National Research and Innovation Agency, 2024)
Industrial development nowadays affects the increase in types of packaging waste which causes the accumulation of waste that has the potential to damage the environment. This research uses an Internet of Things for Automatic Waste Volume Monitoring System, so that waste management in an area can be improved. The purpose of this research is to make it easier for trashman to monitor the volume of the garbage collector on the notification feature. The research method used is the Rapid Application Development methodology with the Requirement Planning stage to analyze and identify the purpose of the system, then design the tools and system and create tools and system. Testing is used to evaluate the results of the tools and system. The result of the research is a prototype of an Internet of Things-based for Automatic Waste Volume Monitoring System tool equipped with a website-based monitoring system and for each user. Apart from that, the system which is equipped with a sensor that can detect the volume of the garbage collector is also equipped with an automatic opening and closing sensor to maintain the health of its users to provide answers to the problem of waste, especially in urban areas. Keywords: Internet of Things, Monitoring System, Waste, Waste Volume.